Effects of buccal acupuncture on postoperative analgesia in elderly patients undergoing laparoscopic radical gastrectomy: a randomized controlled trial - Zhu, Dong-xue; Yang, Yan-ling; Yang, Lei; Zhao, Yuan-yuan; Xie, Ya-yun; Wang, Wei; Lv, Jie; Yu, Wan-you (Frontiers in Neurology, 2024)
Objective This study aimed to evaluate the efficacy and safety of buccal acupuncture on postoperative analgesia, perioperative stress response and adverse events in elderly patients undergoing laparoscopic radical gastrectomy. Methods It was a prospective, outcome assessor-blinded, randomized controlled trial, involving 90 patients aged 65–80 years who were treated with an elective laparoscopic radical gastrectomy. They were randomly assigned to buccal acupuncture group (Group B) and control group (Group C). Buccal acupuncture was applied to patients of Group B before the induction of general anesthesia, while no additional application was given to those in Group C. Patient-controlled intravenous analgesia (PCIA) with sufentanil was postoperatively performed in both groups. Sufentanil consumption and the Visual Analog Scale (VAS) score within 48 h postoperatively were assessed as primary outcomes. Secondary outcomes included peripheral levels of stress markers, intraoperative consumptions of anesthetic drugs and postoperative recovery. Results Patients in Group B presented significantly lower VAS scores within 24 h and less consumption of sufentanil within 48 h postoperatively (both p < 0.01). The awaking time, time to extubation and length of stay were significantly shorter in Group B than in Group C (p = 0.005, 0.001 and 0.028, respectively). Compared with Group C, stress response and inflammatory response within 24 h postoperatively were also significantly milder in Group B. Conclusion The use of buccal acupuncture before general anesthesia induction favors the postoperative analgesic effect and recovery in elderly patients undergoing laparoscopic radical gastrectomy, the mechanism of which involves relieving postoperative stress response and inflammatory response. Clinical trial registration This study was registered in the Chinese Clinical Trial Registry (www.chictr.org.cn) on 15/06/2023 (ChiCTR2300072500).